The gastric H, K-ATPase in stria vascularis contributes to pH regulation of cochlear endolymph but not to K secretion. Issue 1 (December 2017) - Miyazaki, Hiromitsu; Wangemann, Philine; Marcus, Daniel
Abstract Background Disturbance of acid–base balance in the inner ear is known to be associated with hearing loss in a number of conditions including genetic mutations and pharmacologic interventions. Several previous physiologic and immunohistochemical observations lead to proposals of the involvement of acid–base transporters in stria vascularis. Results We directly measured acid flux in vitro from the apical side of isolated stria vascularis from adult C57Bl/6 mice with a novel constant-perfusion pH-selective self-referencing probe. Acid efflux that depended on metabolism and ion transport was observed from the apical side of stria vascularis. The acid flux was decreased to about 40 % of control by removal of the metabolic substrate (glucose-free) and by inhibition of the sodium pump (ouabain). The flux was also decreased a) by inhibition of Na, H-exchangers by amiloride, dimethylamiloride (DMA), S3226 and Hoe694, b) by inhibition of Na, 2Cl, K-cotransporter (NKCC1) by bumetanide, and c) by the likely inhibition of HCO3 /anion exchange by DIDS. By contrast, the acid flux was increased by inhibition of gastric H, K-ATPase (SCH28080) but was not affected by an inhibitor of vH-ATPase (bafilomycin).  K flux from stria vascularis was reduced less than 5 % by SCH28080. Conclusions These observations suggest that stria vascularis may be an important site of control of cochlear acid–base balance and demonstrate a functional role of several acid–base transporters in stria vascularis, including basolateral H, K-ATPase and apical Na, H-exchange. Previous suggestions that H secretion is mediated by an apical vH-ATPase and that basolateral H, K-ATPase contributes importantly to K secretion in stria vascularis are not supported. These results advance our understanding of inner ear acid–base balance and provide a stronger basis to interpret the etiology of genetic and pharmacologic cochlear dysfunctions that are influenced by endolymphatic pH.